Peoples' attitude toward COVID-19 vaccine, acceptance, and social trust among African and Middle East countries - Nasim Asadi Faezi; Pourya Gholizadeh; Moussa Sanogo; Amadou Oumarou; Maad Nasser Mohamed; Yacouba Cissoko; Mamadou Saliou Sow; Bakary Sayon Keita; Youssouf AG Mohamed Baye; Pasquale Pagliano; Patassi Akouda; Sid'Ahmed Soufiane; et al. (Tabriz University of Medical Sciences, 2021)
Background: To end the COVID-19 pandemic, a large part of the world must be immune to the virus by vaccination. Therefore, this study aimed to gauge intent to be vaccinated against COVID-19 among ordinary people and to identify attitudes towards vaccines and barriers for vaccine acceptance. Methods: The study population comprises 1880 people residing in different countries that answer a prepared questionnaire. The questionnaire topics are demographics, historical issues, participants' attitudes and beliefs regarding vaccines, concerns, and vaccine hesitancy. Results: Attitudes and beliefs relating to vaccines in general, and the COVID-19 vaccine, were ascertained. Overall, 66.81% of the contributors would like to be vaccinated against COVID-19, while %33.19 did not intend to be vaccinated. Reasons for COVID-19 vaccine hesitancy included concern regarding vaccine side effects, fear of getting sick from the uptake of the vaccine, and the absence of accurate vaccine promotion news. Individuals with higher education believe that India (68.6%) produces the best vaccine (P<0.001), while healthcare workers think the Chinese vaccine (44.2%) is the best (P=0.020). Individuals with higher education have not been vaccinated, not be healthcare workers, and females were the most contributors to effective of the vaccine in reducing mortality from COVID-19 disease. Conclusion: Given the degree of hesitancy against COVID-19 vaccination, a multifaceted approach to facilitate vaccine uptake that includes vaccine education, behavioral change strategies, and health promotion, is paramount.